(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Sungkai or jati sebrang (Peronema canescens Jack) is one of the industrial timber estate species native to Indonesia, which is commonly chosen for reforestation and as raw materials for the furniture and handicraft industry. In order to provide this planting material in large and sustainable quantities, a technique for in vitro propagation of sungkai through adventitious shoot proliferation is needed and has been successfully developed at the Research Centre for Biotechnology, LIPI. Since tissue culture method is prone to genetic variations, it is important to assess the genetic uniformity of sungkai planting materials derived from this in vitro method at an early stage. In this research, early detection of genetic uniformity was done by morphological observation of the regenerant plants and RAPD analysis using 4 primers namely OPB 5, OPB 9, OPH 11 and OPH 19. Morphological test showed differences in leaf shape, stem diameter and plant height among plantlets originating from Kalbar, Kaltim, Jambi and Cibinong. However, RAPD analysis with PCR showed that all planting materials were genetically uniform among those originating from the same or different places. Â© 2007 Jurusan Biologi FMIPA UNS Surakarta Key words: sungkai (Peronema canescens Jack), perbanyakan in vitro, morfologi, RAPD